2020
DOI: 10.1039/d0tc04221h
|View full text |Cite
|
Sign up to set email alerts
|

A benzoindole-cored building block for deep blue fluorescent materials: synthesis, photophysical properties, and applications in organic light-emitting diodes

Abstract: Deep blue fluorescent materials are crucial in the commercialization of organic light-emitting diodes (OLEDs) for full-color displays or solid-state lighting sources. In this work, a series of aromatic ring compounds...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Benzo[ g ]indole scaffold is used in the synthesis of fluorescent organic molecules that have wide biomedical and technical applications [ 26 , 27 ]. Our interest in the photophysics of the synthesized benzo[ g ]pyrroloimidazoindoles 6 is instigated by the presence of intense long-wavelength ( λ abs (max)~410 nm, ε ≈ 40,000 M −1 cm −1 ) electronic absorption bands with maxima in the violet region and blue photoluminescence, which could make them attractive materials in optoelectronics for blue organic light-emitting diodes (OLEDs).…”
Section: Resultsmentioning
confidence: 99%
“…Benzo[ g ]indole scaffold is used in the synthesis of fluorescent organic molecules that have wide biomedical and technical applications [ 26 , 27 ]. Our interest in the photophysics of the synthesized benzo[ g ]pyrroloimidazoindoles 6 is instigated by the presence of intense long-wavelength ( λ abs (max)~410 nm, ε ≈ 40,000 M −1 cm −1 ) electronic absorption bands with maxima in the violet region and blue photoluminescence, which could make them attractive materials in optoelectronics for blue organic light-emitting diodes (OLEDs).…”
Section: Resultsmentioning
confidence: 99%
“…Metal halide perovskites are regarded as the most promising forefront emissive materials for ultrahigh-definition displays owing to their excellent optoelectronic properties of high photoluminescence quantum yield (PLQY), widely tunable band gap, narrow full-width at half-maximum (FWHM), wide color gamut (140%), and low-cost solution processability. The cutting-edge external quantum efficiencies (EQEs) have exceeded 20% for near-infrared, red, and green perovskite light-emitting diodes (PeLEDs) so far. Nevertheless, the state-of-the-art blue PeLEDs demonstrate an inferior device performance in terms of brightness, EQE, and operational stability. Remarkably, the sky-blue PeLEDs with an emission wavelength of 475–495 nm have obtained peak EQEs in the range of 10%–13.8%, demonstrating the latest advancement of blue PeLEDs. Meanwhile, the display industry urgently needs the saturated blue emission with the wavelength of 467 nm according to the Rec. 2020 standards. , Previous research has found that blue PeLED’s luminous efficiency enormously depends on the emission wavelength as summarized in Table S1, and the best blue PeLED emitting at 467 nm could only reach an EQE of 5.5% by using mixed bromide/chloride perovskites .…”
Section: Introductionmentioning
confidence: 99%